PEDAGOGIA PROIECTULUI: ACTUALITATE ŞI PERSPECTIVE CONCEPTUAL-FUNCŢIONALE - USM ADMIN (Moldova State University, 2011)
The article argues that the project, as a network of meanings, became a significant presence in the educational activity and involves multiple facets formative and sustained cooperation involving intra-and inter-institutional change in order to ensure quality and sustainability, at national and international level. Educational models created through the successful implementation of the project, focusing on results, can replicate in an efficient and relevant in the country and outside it, in whole or in sequence, or experiences acquired, are checked and evaluated, most often, based on indicators of perfor- mance management.